Microlicia delicata and Microlicia pumila (Melastomataceae), two new species from unprotected mountains with campo rupestre vegetation in eastern Brazil - Pacifico, Ricardo; Almeda, Frank; Kriebel, Ricardo (Phytotaxa, 2023)
Two new species of Microlicia are described from the Cadeia do Espinhaço, eastern Brazil. Microlicia pumila is morphologically similar to M. karinae and apparently endemic to Serra da Formosa in northern Minas Gerais. It differs by the delicate branches that are conspicuously verrucose, smaller leaves that are more attenuated along the lower half, smaller hypanthia, calyx lobes, petals and stamens, and by the 3-locular capsules that do not surpass the hypanthial torus at maturity. Microlicia delicata, probably restricted to Três Morros in central Chapada Diamantina, is compared to M. plumosa. It can be recognized by the delicate branches with visible uppermost internodes, shorter leaves that are decussate but not cruciate when branches are seen from above, blades that are straight to somewhat recurved distally and free from each other, shorter calyx lobes and somewhat shorter petals. Morphometric analyses were performed to compare new species to related taxa.